Association studies of the 5-HT2A T102C and the 5-HT2C Cys23Ser receptor gene polymorphisms and suicidal behaviour - Pooley, E; Hawton, K; Houston, K; Harrison, P (2001)
Disruption of the serotonergic system is suggested to be involved in suicidal behaviour and depression. Results from polymorphism studies have been equivocal in their appraisal of a genetic contribution to this involvement. In the current investigation, the frequencies of the 5-HT2A receptor (T102C) and 5-HT2C receptor (Cys23Ser) polymorphisms were examined in a well-characterised sample of deliberate self-harm (DSH) patients and in healthy controls. DSH patients (n= 144) were recruited from the general hospital in Oxford (UK) as part of the WHO/EURO multicentre study on parasuicide. Interviews were conducted using the European Parasuicide Interview Schedule. Additional psychiatric and personality assessments were carried out using structured interview schedules. Controls (currently n = 265; matched for age, gender and ethnicity) were recruited from local blood donation clinics. Genotyping was performed using PCR-based methods (Marshall et al., 1999. Am J Med Genet. 88; 621-7). Allele frequencies were in Hardy-Weinberg equilibrium. Preliminary Chi-squared (cs) analysis of the 5-HT2A (T102 vs. C102: cs = 0.0) and 5-HT2C (Cys23 vs. Ser23: males-cs = 0.38; females-cs = 0.64) revealed no association between allele frequencies and DSH. Within the DSH group there was no association of allele frequencies with either history of major depression or with a composite score for high suicide risk. These results indicate a lack of association between these polymorphisms and suicidal behaviour.